PENGARUH KUALITAS LAYANAN DAN NILAI NASABAH TERHADAP LOYALITAS NASABAH KREDIT DI BPR BATANG PALANGKI KABUPATEN SIJUNJUNG - Saiful Anwar; Radi Putra (LP2M Universitas Bina Bangsa, 2022)
This study aims to examine the quality of service and customer value on credit customer loyalty at BPR Batang Palangki, Sijunjung Regency. This type of research is quantitative, where this study uses numerical data and the research process on measuring objective results using statistical analysis. The population in this study were 500 credit customers at BPR Batang Palangka Raya. The sampling technique used is representative, while the number of samples is 85 people obtained by using the slovin formula. The types of data used in this study are quantitative and qualitative data. While the data sources are primary and secondary data sources. The data analysis technique uses multiple linear regression using SPSS version 21.00 assistance program. The hypothesis was tested using the t test at = 0.05. The results of this study indicate that service quality and customer value have a positive and significant effect on credit customer loyalty at BPR Batang Palangki, Sijunjung Regency